重繪華語語系版圖 - 許, 維賢 (Hong Kong University Press, 2025)
In a work that will force scholars to re-evaluate how they approach Sinophone studies, Wai-Siam Hee demonstrates that many of the major issues raised by contemporary Sinophone studies were already hotly debated in the popular culture surrounding Chinese-language films made in Singapore and Malaya during the Cold War. Despite the high political stakes, the feature films, propaganda films, newsreels, documentaries, newspaper articles, memoirs, and other published materials of the time dealt in sophisticated ways with issues some mistakenly believe are only modern concerns. In the process, the book offers an alternative history to the often taken-for-granted versions of film and national history that sanction anything relating to the Malayan Communist Party during the early period of independence in the region as anti-nationalist.